(untitled) (Fiep Bulletin - online, 2016)
AIDS is currently a pandemic problem that presents regional characteristics and reflects the psychosocial and cultural variables of the population. Considering this, the present research was conducted with the objective of verifying knowledge, attitudes and risk perception regarding HIV/AIDS of Psychology students at a Brazilian university. A structured questionnaire was used, divided into four areas: knowledge about the identity of the HIV, HIV means of transmission, forms of prevention, attitudes and risk perception, and socio-demographics data of the participants. The students presented a good knowledge in relation to the HIV means of transmission and the prevention measures related to HIV/AIDS. However, some data cause concern. An index of only 11.21% of the participants considered as true the statement: “In a health facility, all patients should be considered as potential carriers of HIV”, and only 3.45% of the students answered that they had the necessary professional training to provide care to a person with AIDS. These data point to the lack of preparation of these future health professionals to guide and take care of population, and to the risk of exposure to the HIV. Thus, it is necessary that this matter is treated as a cross-content during the academic years.